SMOKING CESSATION AFTER COUNSELLING IN PATIENTS PRESENTING WITH ACUTE CORONARY SYNDROME - Abbasi, Muhammad Ammad; Malik, Saqib; Ali, Khurshid (Journal of Ayub Medical College Abbottabad, 2018)
Background: The long-term cardiovascular health risks associated with cigarette smoking are well established. It is a major risk factor for all manifestations of coronary artery disease, stroke, and peripheral vascular disease. Patients with acute coronary syndrome, who quit smoking, reduce their risk of cardiovascular events immediately and significantly when compared to those who continue smoking. The study was conducted to determine the frequency of smoking cessation after counselling in patients presenting with acute coronary syndrome (ACS). Methods: Patients of age 35-80 years of either gender presenting with Acute coronary syndrome presented in emergency within 12 hours of symptoms having history of smoking (>1pack year for >5 years) were included in the study. A total 225 patients were enrolled in the study from emergency of Punjab institute of cardiology, Lahore for the duration of six months. Informed consent was obtained from all patients. Their demographic information was also noted. Then patients under went counselling session with researcher himself in presence of psychiatrist from Department of Psychiatry, Services hospital, Lahore. After admitting patients in ward, patients received standard in-hospital treatment for smoking cessation which consisted of an assessment of their smoking behaviour and a personalized brief quit advice. Then patients were followed-up for 12 weeks. On weekly visit, patients were counselled for smoking cessation. After 12 weeks, patients were assessed for cessation of smoking. Results: Smoking cessation was seen in only 37 (16.4%) in ACS patients. Highest frequency of smoking cessation was seen in patients >65 years of age, i.e., 35.1%. Highest frequency for smoking cessation was seen in patients whose BMI was <30 (70.3%), patients with low socioeconomic status (45.9%) and patients with educational status as under matric (40.5%). None of these factors were significantly associated with smoking cessation in patients who presented with ACS. Conclusion: Results of this study demonstrate low frequency of smoking cessation among patients presenting with ACS. However, there is a strong need to identify those factors that were associated with failure to reduce smoking. Keywords: Smoking cessation; Counselling; Acute coronary syndrome